ABDOMINAL WALL COMPLICATIONS OF MISSED GALL STONES IN LAPAROSCOPIC CHOLECYSTECTOMY. - Muhammad Zubair; Lubna Habib; Masoom Mirza (Journal of the Dow University of Health Sciences, 2008)
Port site complications due to lost gall stones in anterior abdominal wall are recently reported complicationsof laparoscopic cholecystectomy. Two cases are hereby reported who had underwent laparoscopiccholecystectomy and later on one presented with discharging sinus and the other with anterior abdominalwall mass. On exploration both the problems were found related to stones lodged in the anterior abdominalwall.